Embedding matrices to extend the shelf life of reference materials 1: Cellulose acetate butyrate. (August 2022) - Toth, Kalman; Hernández, Ana-Maria Sánchez; Bauwens, Jeroen; Buják, Renáta; Marquez, Ramon Carlos; Jakopič, Rožle; Dieste-Blanco, Oliver; Razvan, Buda; Zuleger, Evelyn; Aregbe, Yetunde
Highlights: A shelf life of 3 years can be achieved for large sized dried spikes if cellulose acetate butyrate is used as embedding matrix. With the addition of plasticizer, the shelf life of these mixed nuclear certified reference materials can be extended to at least 4 years. It is important to control environmental conditions during production and suppress acid catalysed hydrolysis. In case the embedding matrix remains intact, the validity of the certificate can be further extended via post certification monitoring, using isotope dilution thermal ionization mass spectrometry. Abstract: The use of a solvent cast film made of cellulose acetate butyrate (CAB) to embed dried actinides is well known and has been applied for about 20 years. Our goal was to improve the initial mechanical properties of CAB films by delaying crack formation and flaking and thereby extending the shelf life of large sized dried (LSD) spike certified reference materials (CRMs). Two different plasticizers, dioctyl phthalate (DOP) and triethyl citrate (TEC), were tested and their influence on static mechanical properties was studied by comparing stress-strain traces. Their thermal behaviour was analysed by Differential Scanning Calorimetry (DSC). DOP overperformed TEC in terms of elasticity and toughness. Visual observation and Scanning Electron Microscopy (SEM) with Energy Dispersive X-Ray Spectroscopy (EDS) analysis was performed as a function of time on four different LSD spikes: the IRMM-1027 series of LSD spike CRMs and three in-house prepared non-certified LSD spikes that differed in terms of most abundant isotopes and actinide mass. It was demonstrated that LSD spike CRMs embedded in a CAB matrix with a DOP plasticizer mass fraction of at least 20% have guaranteed 4 years of shelf life, provided that the embedding film is prepared with great care following protocols for preparation. Acid catalysed hydrolysis should be minimized during the production of the CRM because it could alter the advantageous effects of the plasticizer in the matrix.